Has evolution "prepared" us to deal with death? Paleoanthropological aspects of the enigma of Homo naledi"s disposal of their dead - Du Toit, Cornel W. (HTS teologiese studies, 2017)
The Homo naledi discovery introduced questions that had not been previously posed regarding fossil finds. This is because, apart from their fascinating physiology, they seemingly deliberately disposed of their dead in a ritualised way. Although this theory may still be disproved in future, the present article provisionally accepts it. This evokes religious questions because it suggests the possibility of causal thinking, wilful and cooperative behaviour, and the possibility that this behaviour entails traces of proto-religious ideas. This poses the challenge to develop a hominin hermeneutics that endeavours to reconstruct the possible motivation behind this action. The relatively larger brain with its enlarged Broca’s area suggests the possibility of a sophisticated communication system and an enhanced way of dealing with emotion. We know that almost all life forms have some form of awareness and that more sophisticated degrees of consciousness may be present in the higher primates. Various ‘clues’ are investigated to try and understand the H. naledi phenomenon: lessons from chimpanzee studies, the implications of tool making for hominin development, the possibility of a proto-language and the role symbol formation may have played. The H. naledi case also indicates on a theological level that religion is natural. Some attention is given to this thesis. Biological and environmental factors come into play to illuminate biological factors like emotion and higher cognition without which religion would not be possible. Sophisticated cognition is coloured by affect (basic emotions are typical of all mammals) and this makes some form of reflection on the fate of loved ones who have died a strong possibility.